The Influence of Social Interaction on Social Media, the Quality of Visual Content and Consumer Trust on Buying Interest in Erigo Products through Influencers in the Digital Era - Dewi, Septiana; Sasongko, M. Zuhdi; Hakimah, Ema Nurzainul (Universitas Nusantara PGRI Kediri, 2025)
Research aim : Knowing the influence of social interactions that occur on social media platforms that can affect consumer perception of erigo products, as well as how the quality of visual content presented by influencers can attract attention and form consumer trust in the digital era. Design/Methode/Approach : This study uses a quantitative method. The sample in this study was 40 respondents who were selected using the purposive sampling technique, namely consumers who have known and used Erigo products. Data were collected through a questionnaire with a Likert scale and analyzed using multiple linear regression with the help of SPSSv23. Research Finding : The results of the study showed that social interaction on social media did not have a significant effect on the interest in buying Erigo products through influencers with a significance value of 0.577. Meanwhile, the quality of visual content, and consumer trust significantly influenced the buying interest of Erigo products through influencers, with significance values of 0.000 and 0.003 respectively. Theoretical contribution/Originality : To improve the understanding of social interaction on social media, the quality of visual content and consumer trust in the digital era, especially in marketing involving influencers. Practitionel/Policy implication : The findings of this study Erigo need to pay attention to the quality of visual content and build positive social interactions on social media platforms to increase consumer trust and buying interest. Research limitation : This study has a limited sample size of only 40 respondents and uses a non-probability sampling technique, so the results of the study may not be applicable in general to a larger population